2014
DOI: 10.4236/jwarp.2014.62020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Consumption and the Development of Skeletal Fluorosis in a Fluoride Endemic Area of the Ethiopian Rift Valley

Abstract: This study compared the occurrence of skeletal fluorosis in chronic consumers of locally brewed alcoholic beverages and their matched controls in the Ethiopian Rift Valley. The study revealed that chronic alcohol consumers developed severe forms of crippling skeletal fluorosis quite early in life. The controls were either symptom-free or exhibited mild forms of the fluorosis. The study showed that crippling skeletal fluorosis was directly associated with the large volumes of the locally brewed beer and honey-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…A significant part of this ingested fluoride is contained in beverages, including alcoholic drinks, a quantitatively significant component of the diet of many people and the primary source of exogenous ethyl alcohol [ 3 ]. Because of their prevalence and volume of consumption, they should be considered a potential source of other xenobiotics and taken into account in preparing a balanced diet [ 4 ]. Due to the continuing controversy over the use of fluorine compounds in the prevention of tooth decay and the possible adverse effects (fluorosis), it seems prudent to examine the presence of fluoride in common food products, including alcoholic beverages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant part of this ingested fluoride is contained in beverages, including alcoholic drinks, a quantitatively significant component of the diet of many people and the primary source of exogenous ethyl alcohol [ 3 ]. Because of their prevalence and volume of consumption, they should be considered a potential source of other xenobiotics and taken into account in preparing a balanced diet [ 4 ]. Due to the continuing controversy over the use of fluorine compounds in the prevention of tooth decay and the possible adverse effects (fluorosis), it seems prudent to examine the presence of fluoride in common food products, including alcoholic beverages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic water testing in the Ziway-Shala basin of the MER has shown that F − concentrations can reach up to 68 mg/L (mean: 9.4 ± 10.5 mg/L), and that F − levels in 94% of the tested wells exceeded the World Health Organization (WHO) standard of 1.5 mg/L (Rango et al, 2012). In this region, an estimated 8.5 million people, mostly from rural communities, are highly dependent on groundwater resources for drinking and domestic purposes and are thus at risk of fluorosis (Tekle-Haimanot et al, 1987;Tekle-Haimanot, 2005;Tekle-Haimanot and Haile, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Strong dynamic flow in highland areas flush away weathered chemical components (e.g., F − ). Thus, surficial weathering is not a major controlling factor for high concentrations of Fluoride in deep groundwater but the combination of silicate hydrolysis and ion exchange mainly control fluoride enrichment in stagnant flow environments.In past decades, researchers have studied the geographical distribution of fluoride concentration [6-8] and its relationship with dental caries, dental fluorosis and skeletal fluorosis [9][10][11] in the Ethiopian rift valley. Water quality and fluoride sources were investigated in the central Ethiopian rift [12].…”
mentioning
confidence: 99%
“…In past decades, researchers have studied the geographical distribution of fluoride concentration [6-8] and its relationship with dental caries, dental fluorosis and skeletal fluorosis [9][10][11] in the Ethiopian rift valley. Water quality and fluoride sources were investigated in the central Ethiopian rift [12].…”
mentioning
confidence: 99%